Canada : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2016)
This report summarizes the anti-money laundering and combating the financing of terrorism measures in place in Canada. The Canadian authorities have a good understanding of most of Canada's money laundering and terrorism financing risks. Some financial intelligence and other relevant information are accessible by the Financial Transactions and Reports Analysis Centre of Canada (FINTRAC); law enforcement agencies have greater access. FINTRAC receives a wide range of information, which it uses adequately, but some factors limit the scope and depth of the analysis it is authorized to conduct.